Judicial Independence under Threat - Giannoulopoulos, Dimitrios (Proceedings of the British Academy Series, 2022)
Judicial Independence Under Threat seeks to situate contemporary challenges to judicial independence in their proper legal, philosophical, political and historical contexts. It asks how threats to judicial independence can be protected against.